Design and construction of a machine for micro-abrasioncorrosion testing in simulated biological environments - Caballero, José Luís; Sierra Melo, Nicolás; Aperador Chaparro, William (TECCIENCIA, 2016)
Medicine and engineering have generated advances in reducing the adverse effects of biomaterials on the human body. However, joint replacements remain a subject of interest since they present various failures stemming from wear processes and corrosion phenomena. Additionally, the growing demand for these devices by ever younger people and the increase in life expectancy generate the necessity of implants with a longer service life. To satisfy this need, all factors that influence joint replacement deterioration must be studied. This study therefore describes a method to design and manufacture equipment that performs simultaneous micro-abrasion and electrochemical tests on various materials in simulated biological fluids for the purpose of observing their behavior and viability as a biomaterial. Despite the availability of analogous equipment abroad and the low investment in research in our country, Colombia, affordable technology which focuses on aspects of greatest relevance for stakeholders and may bring the greatest impact can indeed be developed. Thus, with the implementation of design techniques, software tools such as Catia, and interdisciplinary knowledge, the conceptual and detailed design of the system and its later construction were achieved.